2014
DOI: 10.2215/cjn.05750513
|View full text |Cite
|
Sign up to set email alerts
|

Medication Treatment Complexity and Adherence in Children with CKD

Abstract: SummaryBackground and objectives The complexity of CKD management in children is increased by the number of comorbid conditions. This study assessed the prevalence of comorbidities in pediatric CKD and the frequency with which multiple comorbidities present together by assessing prevalent medication use by CKD stage and diagnosis and their association with clinical or sociodemographic factors. The association between number and frequency of dosing of medications prescribed and self-report of nonadherence was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 23 publications
3
33
0
1
Order By: Relevance
“…To evaluate the knowledge of the child/adolescent and/or family about the health condition (18)(19)(20) Question the child/adolescent and/or his/her family about their strategies for self-care (19,21) Ask the child/adolescent and/or family what are the barriers to self-care (21)(22)(23) To assess the importance and degree of confidence of the child/ adolescent and/or family for self-care (19) To evaluate the child/adolescent and/or family adherence in activities present in the self-care plan (17,(24)(25)(26)(27)(28)(29) To evaluate the capacity of the patients and/or family to perform an intervention (14,19,30) To determine the strategies used by the child/adolescent with chronic disease for rehabilitation/coping (21,31) To assess the emotional state (depression, mood, anxiety, etc.) of the child/adolescent and/or the family, which may influence self-care actions (13,17,23,30,(32)(33) To evaluate the process of health care transition (HCT) from pediatric to adult-centered health care delivery systems (16,18,21,(34)(35) Counseling Inform the child/adolescent and/or family about the symptoms of the disease and/or therapeutic measures (17,27,36) , while recognizing the cultural uniqueness (19) Inform the child/adolescent and/or family that behavioral changes are as important as taking medications (20) To report the evidence on behavioral changes in health …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the knowledge of the child/adolescent and/or family about the health condition (18)(19)(20) Question the child/adolescent and/or his/her family about their strategies for self-care (19,21) Ask the child/adolescent and/or family what are the barriers to self-care (21)(22)(23) To assess the importance and degree of confidence of the child/ adolescent and/or family for self-care (19) To evaluate the child/adolescent and/or family adherence in activities present in the self-care plan (17,(24)(25)(26)(27)(28)(29) To evaluate the capacity of the patients and/or family to perform an intervention (14,19,30) To determine the strategies used by the child/adolescent with chronic disease for rehabilitation/coping (21,31) To assess the emotional state (depression, mood, anxiety, etc.) of the child/adolescent and/or the family, which may influence self-care actions (13,17,23,30,(32)(33) To evaluate the process of health care transition (HCT) from pediatric to adult-centered health care delivery systems (16,18,21,(34)(35) Counseling Inform the child/adolescent and/or family about the symptoms of the disease and/or therapeutic measures (17,27,36) , while recognizing the cultural uniqueness (19) Inform the child/adolescent and/or family that behavioral changes are as important as taking medications (20) To report the evidence on behavioral changes in health …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated this activity (13)(14)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) . One of the aspects discussed in the research was to determine whether activities for self-care management are adhered to along with therapies and skills already developed by health professionals (17,(24)(25)(26)(27)(28)(29) . Thus, studies in pediatrics have demonstrated a significant association between nonadherence and the frequency of medication use; since medications that needed to be taken more frequently during the day were subject to higher rates of nonadherence (24,28) , this together with the number of tablets ingested per dose (28) .…”
Section: Discussion Evaluationmentioning
confidence: 99%
“…In our study, children with short stature had a higher prevalence of Medicaid use, which may be a marker of lower socioeconomic status that could partially explain the higher mortality risk in shorter children despite transplantation. Other factors such as nonadherence to therapy and lower access to care, which are commonly associated with short stature in children with CKD (19)(20)(21), may also be underlying factors that could contribute to the elevated mortality risk in children with short stature.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of patients with CKD includes multiple medications, high dosing frequency, numerous dose adjustments due to disease progression, and the need for coordination of medication administration timing with meals, all of which create a unique context for medication nonadherence in children (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…A recent Canadian study, based on the pharmacy refill rates in a pediatric CKD cohort, demonstrated that on average, patients missed 1 day of medications each week (20). A cross-sectional analysis of baseline CKiD data indicated that medications thought to support optimal growth were among those with the highest rates of nonadherence (21). However, the extent of medication nonadherence in children with CKD over time and its association with poor growth remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%